Advances in spatial and temporal databases : 15th International Symposium, SSTD 2017, Arlington, VA, USA, August 21-23, 2017, Proceedings /: 15th International Symposium, SSTD 2017, Arlington, VA, USA, August 21-23, 2017, Proceedings. (2017) - Unknown
No abstract available